Las Reglas de Rotterdam (II) - Llorente Gómez de Segura, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
This article is the second from a successive series of articles on the Rotterdam Rules which started to be published in No 1, Volume 2 of Cuadernos de Derecho Transnacional (March 2010), pages 165-185. Now, following the outline advanced in Part I, our comments will be focused on the analysis of the formal and documentary aspects contained in the regulation of the Rotterdam Rules as applied to the contract for the international carriage of goods wholly or partly by sea. Through a classical exposition approach, we will address issues such as the concept and classes of transport documents contemplated by the Rules, their issuance and signature, their contents and their functions.